Incropera's principles of heat and mass transfer - Bergman, T. L.; Lavine, Adrienne; DeWitt, David P.; Incropera, Frank P. (John Wiley & Sons, 2017)
Applying the rigorous and systematic problem-solving methodology pioneered by this text, an abundance of examples and problems reveal the richness and beauty of the discipline. This edistion makes heat and mass transfer more approachable by giving additional emphasis to fundamental concepts, while highlighting the relevance of two of today's most critical issues : energy and the environment.